A Journey of Functional Test Evolution in the Public Sector - Souza, Bruno Pedraça de; Motta, Rebeca Campos; Costa, Jessica Soares da; Nunes, Elaine; Pinto, Gustavo Rocha Barreto; Mello, Rafael Maiani de (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2025: Anais do X Simpósio Brasileiro de Testes de Software Sistemático e AutomatizadoDO - 10.5753/sast.2025.13869, 2025)
Since 2015, a public legal institution in Brazil has relied on a large-scale information system to support its services. As the system's complexity and business relevance increased over the years, functional testing evolved from an ad-hoc, manual approach to a systematic, automated practice integrated into the development workflow. This paper reports on the evolution of the maturity stages, detailing the challenges encountered and key milestones achieved by adopting Selenium IDE automated tool testing. It also presents the main lessons learned by the testing team over this long-term process. Notably, process adjustments, regression testing strategies, and the adoption of Selenium IDE were instrumental in enhancing software quality. By sharing this trajectory, we aim to provide practical insight into other institutions facing similar constraints and demands.